Penerapan Prinsip Tata Pemerintahan Yang Baik Dalam Pelayanan Publik Di Kantor Kesyahbandaran Dan Otoritas Pelabuhan Kelas II Samarinda - ST. Nurhasanah; Syachrul Syachrul; Annisa Nindia Putri (Politeknik Negeri Samarinda, 2022)
Given the current state of public services, the principles of good governance must be followed to achieve the desired organizational results. To achieve this goal, it is very important to support human resources, namely personnel who demonstrate qualities and attitudes that are in accordance with the principles of Good Governance Principles. This study aims to find out and examine how to apply the principles of good governance in the public service section of sailing safety, guarding, and patrolling types of sailing approval letter services at the Samarinda Class II Harbor Authority and Harbor Authority whether it has been running well or not. qualitative method with descriptive research type. Data collection techniques used through observation, interviews, and documentation. The number of informants in this study amounted to 9 people. Based on the research, it is known that the application of the principle of transparency at the Office of the Harbor Master and the Port Authority of Samarinda is still quite good, because the services received by the community are good from clear information disclosure in writing and orally to service users regarding procedures, requirements in managing the service of a pay approval letter at the Harbormaster Office. and the Samarinda Class II Port Authority. Principle The responsiveness of the Samarinda Port Authority and Harbormaster Office employees is good, this is because the officers serve quickly. The principle of fairness for employees at the Office of the Harbor Master and the Samarinda Port Authority is good enough to need to be maintained and improved in providing services to service users